Du fictionnel à l’autofictionnel ? - Bertrand Tassou (Itinéraires)
From 2004 to 2011, Patrick Deville published (Éditions du Seuil) a novel tetralogy. This well-structured, coherent project is dedicated to eras, places and characters that are often neglected by occidental historiography. However, these texts prove to be unclassifiable: although they are habitually connected to historical investigations, they often invent: these are also travel stories that may play with autofiction codes.